Intermarriage from Central Europe to Central Asia : Mixed Families in the Age of Extremes - Edgar, Adrienne Lynn, 1960- (Book collections on Project MUSE., 2020)
"Edgar and Frommer bring together international and interdisciplinary scholarship to analyze interethnic and interracial marriage in Eastern Europe, the former Soviet Union, and Central Asia"--